CPW-Fed KOCH SNOWFLAKE Fractal Antenna for UWB Wireless Applications - Reha, Abdelati; El Amri, Abdelkebir; Benhmammouch, Othmane; Oulad Said, Ahmed (Discoveries in Agriculture and Food Sciences, 2014)
Four iterations of a Coplanar Waveguide (CPW)-Fed KOCH SNOWFLAKE fractal antenna are studied. Increasing the number of iterations allows us obtaining a miniaturized antenna with high gain, multi-band and broad-band behavior. The proposed antennas are a good solution for the Ultra Wide Band (UWB) applications and for the 3.7-4.2GHz C-Band, 5.15-5.82 GHz Wireless Local Area Network (WLAN), and for the 5GHz Worldwide Interoperability for Microwave Access system (WIMAX) applications. The simulation was performed in FEKO 6.3.